(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the use of case terms in the Kyrgyz and Uzbek languages, namely, using examples of how phonetic homonymy is implemented in the dialects of both languages. In particular, based on the research of scientists, the use of a falling penis in earning abilities is analyzed.